Why Work? Why Not! Older Adults Tell It Like It Is: What Baby Boomers, Adult Educators, and Management Can Learn From Current Older Workers and the Role of Ageism in the Workforce - Kathy M. Bonnar (Adult Education Research Conference, 2013)
This roundtable seeks to look at the older adult worker and what they bring to the workforce. The U.S. Bureau of Labor Statistics projects that the older adult workers’ numbers will be increasing to roughly 22% of the labor force through 2050. The older adult worker is definitely here to stay. How they feel about work and what they have to offer as older workers will surely impact the workforce. What we as educators and management can learn from them now will be essential to the older adult worker’s successful employment.